Gastroesophageal varices evaluation using spleen‐dedicated stiffness measurement by vibration‐controlled transient elastography. Issue 1 (14th December 2021) - Nagai, Koki; Ogawa, Yuji; Kobayashi, Takashi; Iwaki, Michihiro; Nogami, Asako; Honda, Yasushi; Kessoku, Takaomi; Saigusa, Yusuke; Imajo, Kento; Yoneda, Masato; Kirikoshi, Hiroyuki; Komatsu, Tatsuji; et al.
Abstract: Background and Aim: Liver stiffness measurement (LSM) and spleen stiffness measurement (SSM@50 Hz) using standard vibration‐controlled transient elastography (VCTE) have been studied as a noninvasive test for screening of gastroesophageal varices (GEV) in chronic liver disease (CLD). Recently, a novel spleen‐dedicated VCTE (SSM@100 Hz) has been developed. We evaluated the diagnostic performance of SSM@100 Hz, SSM@50 Hz, LSM, and other noninvasive tests using esophagogastroduodenoscopy (EGD) as the reference as well as the correlation with hepatic venous pressure gradient (HVPG). Methods: A total of 123 patients with CLD enrolled in this cross‐sectional study. SSM@100 Hz, SSM@50 Hz, and LSM were determined by VCTE. EGD and HVPG were performed within 12 weeks before or after VCTE. Results: GEV were present in 60 patients. Failure or suboptimal SSM were fewer at 100 Hz (4.0%) than at 50 Hz (17.7%). All SSM values obtained at 100 Hz were lower than the 100 kPa ceiling threshold, but 10 patients reached the 75 kPa ceiling threshold for SSM@50 Hz. SSM@100 Hz was most accurate (area under the receiver operating characteristic [AUROC] = 0.944) for the diagnosis of GEV compared to SSM@50 Hz, LSM, and scoring systems. AUROC of SSM@100 Hz for diagnosis of high‐bleeding risk varices (HRV) was 0.941, which was significantly higher than that of SSM@50 Hz (AUROC = 0.842, P  = 0.002). SSM@100 Hz showed higher specificity (82.0%) for diagnosis of HRV than SSM@50 Hz (specificity = 67.1%). SSM@100 Hz was significantly correlated with HVPG ( r  = 0.71, P  < 0.001). Conclusions: The novel spleen‐dedicated VCTE examination can be used for noninvasive assessment of GEV and HVPG in CLD. Japan Registry of Clinical Trials Registry No. jRCTs032200119. Abstract : The novel spleen‐dedicated vibration‐controlled transient elastography examination can be used for noninvasive assessment of gastroesophageal varices and hepatic venous pressure gradient in chronic liver disease.